2017
DOI: 10.1016/j.jmii.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcomes of cytomegalovirus viremia in pediatric hematopoietic stem cell transplantation patients

Abstract: In pediatric posttransplantation patients, CMV viremia mostly occurred within 100 days after transplantation. Risk factors associated with CMV viremia include older diagnostic age, leukemic patients, unrelated donor HSCT, pretransplant ATG use, GvHD, and gastrointestinal GvHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 26 publications
4
31
2
5
Order By: Relevance
“…A higher degree of immunosuppression might be the key factor for the increased CMV infection risk in haploidentical allo‐HSCT. Among the immunosuppressants administered to haploidentical recipients, ATG is highly related to CMV infection in allo‐HSCT . A comparable result was obtained in the univariate analysis in our study, but not in the multivariate analysis, which showed that ATG does not significantly increase the risk of CMV DNAemia (HR: 1.32; 95% CI: 0.50‐3.51; P = 0.571).…”
Section: Discussionsupporting
confidence: 81%
“…A higher degree of immunosuppression might be the key factor for the increased CMV infection risk in haploidentical allo‐HSCT. Among the immunosuppressants administered to haploidentical recipients, ATG is highly related to CMV infection in allo‐HSCT . A comparable result was obtained in the univariate analysis in our study, but not in the multivariate analysis, which showed that ATG does not significantly increase the risk of CMV DNAemia (HR: 1.32; 95% CI: 0.50‐3.51; P = 0.571).…”
Section: Discussionsupporting
confidence: 81%
“…Viral infections are frequently encountered in pediatric patients undergoing hematopoietic stem cell transplant (HSCT) and are associated with significant morbidity and mortality. Clinical risk factors have been described during different periods post‐HSCT as contributing factors for the reactivation and/or primary acquisition of several viral infections among children . Viral reactivations in children are frequent especially following allogeneic transplantation (allo‐HSCT), while in autologous transplantation (auto‐HSCT) they have not been investigated in detail possibly due to the lack of routine surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Lilleri ve arkadaşları 178 allojenik HKHT alıcısında CMV viremisini %34, buna karşılık CMV antijenemisini %42 oranında daha yüksek tespit ederek kantitatif real-time PCR testinin uygulanmasının gereksiz antiviral tedaviyi önleyeceğini bildirmişlerdir [20] . Wu ve arkadaşları-nın çalışmasında HKHT uygulanan 57 çocuk hastadan %32 (18 hasta)'sinde CMV viremisi geliş-miştir ve bu olguların %89 (16/18)'unda ilk 100 günde infeksiyon ortaya çıkmıştır [21] . Hiwarkar ve arkadaşlarının araştırmasında allojenik HKHT yapılan 291 çocuk hastanın %16'sında CMV, %15'inde ADV ve %11'inde EBV infeksiyonu gelişmiştir [22] .…”
Section: Discussionunclassified
“…Çalışma grubumuzda miyeloablatif ve yoğunluğu azaltılmış hazırlama rejimi uygulanmış hastalarda CMV DNA (sırasıyla 32-8. Allojenik HKHT alıcısı 46 çocukta %26 oranında bulduğumuz CMV infeksiyonu insidansı Paris'in (%26.8) bulgusuna benzer, Hiwarkar (%16) ve Goldstein'in (%21) verilerinden biraz yüksek-tir, buna karşılık Gomes (%44), Lilleri (%34) ve Wu'nun (%32) bildirdiği oranlardan düşüktür [18][19][20][21][22][23] .…”
Section: Discussionunclassified
See 1 more Smart Citation